(untitled) (International Journal of Sustainable Development & World Policy, 2014)
The focus of this study is to identify the cross sectional point of view by applying Critical Success Factors (CSFs) into entrepreneurship programs in Community colleges under the supervision of Ministry of Education (MOE). Entrepreneurship Program is regarded as a transformation effort in trying to create new entrepreneurs and indirectly reduce the unemployment rate. It is also regarded as a program that would enable students to compete locally and globally in an era where competition is inevitable. Critical Success Factors is widely used tool in business in to aid the organisation to identify the factors that constitutes to a success of a given project. The four elements of Critical Success Factors (CSFs); which was introduced by Rockart 1979 are Industry, Strategy, Environment and Temporal are engaged by organizations or projects in order to achieve the desired outcome. Hence this paper sets out to investigate the elements of CSFs and adapt the elements to the entrepreneurship programs conducted in the community college. Therefore this CSFs provides academic scholars and industry practitioners a deeper knowledge of CSFs and necessary guidelines to utilise the elements in the programs.